THE PRINCIPLE OF AMANAH IN THE UTILIZATION OF CONSUMER’S PERSONAL DATA AND INFORMATION IN OPEN BANKING - Prasastinah Usanti, Trisadini (Journal of Central Banking Law and Institutions, 2022)
Banks are generally prohibited in any possible way from providing customers’ data or information to third parties unless there is a written consent from the customer, or it is required by laws or regulations. Open banking allows banks to obtain customer financial data and information and forward them to third parties to accelerate a digital transformation in banking. The existence of the customer’s consent resulted in the bank’s legal action providing customer data and information to a third party is not considered as a violation to the principle of confidentiality. However, the provision of customer data by banks to third parties must be based on the fiduciary principle, prudential principle, and principle of amanah, since the misuse of customers’ data can lead to administrative sanctions, criminal sanctions, and civil liability.